A qualitative investigation into the rehabilitation experience of patients following wrist fracture - Bamford, Rachael; Walker, Dawn-Marie (Royal Society of Medicine Press, 2010)
Introduction. Fractures of the wrist are often highly traumatic, leading to significant pain and reduction in an individual’s home, work and leisure roles for a considerable time. Among the studies on wrist fracture, there is limited evidence which qualitatively explores the patient’s rehabilitation experiences of this condition, and the impact they feel it has on their daily lives. The aim of this study was therefore to explore the experiences of working age people with dominant side wrist fracture in terms of the impact on their lives from the resulting loss of hand function, and the role that hand therapy plays in the rehabilitation process. Method. Using a qualitative approach, semistructured interviews were carried out with six participants who were current or previous patients of an outpatient occupational therapy department and who had sustained wrist fracture. Three key themes equated to the impact the fracture had on their lives: ‘functional ability’, ‘attitudes and expectations of self and others’ and ‘assessment and treatment in occupational therapy’. Results. The main findings showed that the impact of reduced ability evoked negative reactions and dependence on others. Lack of information on application and removal of plaster cast contributed towards early anxieties about the appearance and function of the hand. Patients’ attitudes generally reflected taking some responsibility for their own progress. Occupational therapy input increased motivation, and particularly for those who attended rehabilitation sessions in the department, the therapy was valued. Discussion. The recommendations from this study are that early and continued patient education is provided by the therapist, engaging relatives where appropriate, to alleviate patient and family anxieties and to help determine realistic expectations of recovery. While patients generally engage with objective measurements, making assessment and treatment relevant to their activities of daily living is essential to ensure they are motivated for therapy.